Structural behavior of high-strength concrete corbels involving steel fibers or closed stirrups (Periodicals of Engineering and Natural Sciences, 2022)
A comprehensive experimental evaluation of the shear behavior of corbels made by high-strength concrete (HSC) with steel fiber or with stirrups was investigated. Thirteen samples were prepared and tested, the main variables in this research were steel fiber type, steel fiber content (Vf %), and amount of horizontal closed stirrups (Ah). The constants in this investigation were the area of the main steel reinforcement (As), ratio of shear span to depth (a/d) and cube concrete strength (fcu). The obtained results clearly showed that, the presence of fibers or closed stirrups enhanced the strength and decreased the deformation of the explored specimens. It was concluded that the horizontal shear reinforcement can be substituted by supplementation of steel fibers to RHSC corbels. A comparison was performed between the test results and estimated shear capacity by ACI code and other adopted equations. Very conservative shear strength values were obtained from ACI 318–19 for corbels prepared with high-strength concrete because the strut and tie method were influenced by concrete strength and did not take the contribution of closed stirrups into account. However, the shear friction method depends only on the quantity of the main steel reinforcement and closed stirrups. Russo [2] proposed a model that adequately predicted the ultimate force of high-strength RC corbels incorporating closed stirrups, but this model did not take the effect of steel fibers into account. Campione [3] added the effect of steel fibers by means of the residual tensile strength expression.